1984
DOI: 10.1083/jcb.98.1.222
|View full text |Cite
|
Sign up to set email alerts
|

Insulin, not C-peptide (proinsulin), is present in crinophagic bodies of the pancreatic B-cell.

Abstract: We have obtained evidence by autoradiography and immunocytochemistry that mature secretory granules of the pancreatic B-cell gain access to a lysosomal compartment (multigranular or crinophagic bodies) where the secretory granule content is degraded . Whereas the mature secretory granule content shows both insulin and C-peptide (proinsulin) immunoreactivities, in crinophagic bodies only insulin, but not C-peptide, immunoreactivity was detectable . The absence of C-peptide (proinsulin) immunoreactivity in multi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
110
0
2

Year Published

1985
1985
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(121 citation statements)
references
References 27 publications
9
110
0
2
Order By: Relevance
“…The importance of this finding is that the antibody exclusively reacts with the B chain peptide and not with native insulin, indicating that some intracellular vesicles contain degradative products of insulin. Extensive studies have unequivocally shown that beta cells contain vesicles bearing insulin catabolites, in a pathway referred to as crinophagy (32)(33)(34)(35)(36). It indicates an intracellular degradation of excess insulin granules, as a mode of controlling the homeostasis of insulin granule content (32,37).…”
Section: Live Imaging Of Beta Cells and Apcs And Electron Microscopymentioning
confidence: 99%
“…The importance of this finding is that the antibody exclusively reacts with the B chain peptide and not with native insulin, indicating that some intracellular vesicles contain degradative products of insulin. Extensive studies have unequivocally shown that beta cells contain vesicles bearing insulin catabolites, in a pathway referred to as crinophagy (32)(33)(34)(35)(36). It indicates an intracellular degradation of excess insulin granules, as a mode of controlling the homeostasis of insulin granule content (32,37).…”
Section: Live Imaging Of Beta Cells and Apcs And Electron Microscopymentioning
confidence: 99%
“…Physiological roles of crinophagy and autophagy Pioneering studies by Orci et al showed that insulin granules are regulated by lysosomal degradation through crinophagy and autophagy [61]. In crinophagy, the secretory granule membrane fuses with the membrane of a large vacuolar, lysosomal compartment to generate a crinophagic body, within which the insulin granule content is degraded.…”
Section: Autophagy In Beta Cell Physiology and Diabetesmentioning
confidence: 99%
“…Insulin granules may also reach lysosomes via autophagosomes that engulf cytosolic components containing secretory granules (macroautophagy), or via lysosomal engulfment and swallowing of a single granule (microautophagy). Insulin is relatively resistant to degradation in the acidic environment of the lysosome; its degradation is much slower than that of C-peptide or proinsulin [61,62]. This underlies the assumption that insulin degradation plays a minor role in the regulation of insulin homeostasis and beta cell function [62].…”
Section: Autophagy In Beta Cell Physiology and Diabetesmentioning
confidence: 99%
“…In the B cell, morphological evidence for crinophagy consists of cytoplasmic organelles of variable morphology containing dense masses resembling t-secretory granule cores. The lysosomal nature of these structures (also called crinophagic or multigranular bodies) is evidenced by their content in lysosomal enzymes such as acid phosphatase, arylsulfatase [35] or cathepsin B (Fig. 11 C).…”
Section: (Pro)insulin Degradationmentioning
confidence: 99%
“…11 C). Whether or not the granule core-like material of multigranular bodies is related to insulin polypeptides has recently been explored by immunocytochemistry at the ultrastructural level using anti-insulin and anti-C-peptide antisera [35]. A timetable of the postulated transfer of secretory granule cores into lysosomal structures was also assessed by pulse-chase experiments with 3H-leucine on isolated islets.…”
Section: (Pro)insulin Degradationmentioning
confidence: 99%